A ZoomTree interface for searching genealogical information - Wesson, Janet; du Plessis, MC; Oosthuizen, Craig (AFRIGRAPH'04: Proceedings of the International Conference on Computer Graphics, Virtual Reality, Visualisation and Interaction in Africa, 2004)
Genealogical information systems (GIS) typically contain large amounts of information about families and relationships between family members. Most existing GIS have textual, form-based interfaces for searching and browsing family information. These interfaces do not support dynamic browsing and manipulation of family trees. This paper discusses the design and development of a novel interface, called ZoomTree, for WINGIS (the GIS developed at UPE), to facilitate dynamic exploration and browsing of family tree information.